SECURITY SYMBOLS: INTEGRATING CRYPTOGRAPHY WITH CYBER SECURITY TO PROTECT DIGITAL SYSTEMS - Mykhailyshyn , Kateryna; Opirskyy, Ivan (Ukrainian Information Security Research Journal, 2024)
Cyber security is a set of procedures aimed at protecting computer systems, networks and data from unauthorized access. In today's digital environment, cyber security has become critical for business, administration and management, as well as for private individuals, as threats from cyber attacks are ever increasing. The modern world is inextricably linked with the latest technologies that permeate all spheres of our lives. However, the growing dependence on digital technologies leads to cyber threats that can affect the security and stability of society. Integrating cryptography with cybersecurity is the answer to these challenges. A strategic approach to ensuring the security of information technology is the integration of cryptography, which is based as security against unauthorized access and to ensure authentication and inaccessibility of data or systems. The merger of cryptography with cyber security allows to create a comprehensive approach to the protection of digital systems, taking into account modern risks and problems. The increase in the number and complexity of threats requires constant improvement of methods that will allow adapting to modern and future attacks, ensuring effective protection of digital systems and the relevance of the problem in today's digital world. Let's consider the importance of the role of the human factor in ensuring cyber security and possible approaches to take this aspect into account when developing and implementing cryptographic solutions. In addition, an analysis of Ukrainian qualified electronic signatures is conducted, which is an improved form of electronic signature, ensuring a high level of protection and authenticity of electronic documents in a technological environment.